2023
DOI: 10.1002/cam4.6001
|View full text |Cite
|
Sign up to set email alerts
|

Learning from long‐term adolescent and young adult (AYA) cancer survivors regarding their age‐specific care needs to improve current AYA care programs

Abstract: Background Despite growing (inter)national awareness and appreciation, age‐specific care is still not always self‐evident and accepted as standard of care for adolescent and young adult (AYA) cancer patients. It is unknown whether long‐term AYA cancer survivors have missed age‐specific care, and if so, which survivors missed it and regarding which topics. Methods The Netherlands Cancer Registry (NCR) identified all long‐term AYA cancer survivors (aged 18–39 years at initial cancer diagnosis, 5–20 years past di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Sexuality and intimacy are important aspects of AYA health care and sexual health should be discussed early in the treatment process. 35 , 78 The results of this study demonstrated that AYA breast cancer survivors experience significantly more sexual QoL challenges compared to (female) AYA survivors of other cancer types. While discussing that sexual health is important for all AYA cancer survivors, those facing challenges related to sexuality, particularly breast cancer patients, might benefit from specialized interventions such as consultations with a sexologist.…”
Section: Discussionmentioning
confidence: 70%
“…Sexuality and intimacy are important aspects of AYA health care and sexual health should be discussed early in the treatment process. 35 , 78 The results of this study demonstrated that AYA breast cancer survivors experience significantly more sexual QoL challenges compared to (female) AYA survivors of other cancer types. While discussing that sexual health is important for all AYA cancer survivors, those facing challenges related to sexuality, particularly breast cancer patients, might benefit from specialized interventions such as consultations with a sexologist.…”
Section: Discussionmentioning
confidence: 70%
“…Young adults with cancer are exposed to disease- and treatment-related stressors as well as various psychosocial stressors [ 27 , 70 ]. Existing psycho-oncological research shows that AYA have unmet needs for information and support [ 71 , 72 ]. Social support is crucial for this patient group, and in addition to family and friends, social interactions with peers play an important role [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…With continued professional development and recruitment of additional interdisciplinary team members; the current “domains” of AYA supportive care include fertility preservation, sexual health, spirituality, finances, school, work, symptom management, diet, exercise, sleep, relationships, parenting, coping, peer connection, and practical support. The flow of patients through the AYA program, including which actions are carried out by specific team members is shown in ( Figure 1 ) [ 38 ].…”
Section: The Program Development Processmentioning
confidence: 99%